Застосування теорії центральних місць в археології для визначення відносних дат і розмірів поселень - Дяченко, О.В. (Археологія, 2011)
Використання символьного вираження теорії центральних місць М. Бекманна дозволяє встановити кількість та розміри поселень, відсутніх у добірках. Спеціальне застосування теорії центральних місць може слугувати для відносного датування відомих поселень, визначення їхніх орієнтовних розмірів і розвідок нових пам’яток. Специфика применения методов пространственного анализа в археологии зачастую связана с неполнотой информации о системах расселения прошлого. Использование символьного выражения теории центральных мест М. Бэкманна позволяет установить размеры и количество отсутствующих в выборках населенных пунктов. Связать с ними конкретные памятники, не имеющие четких относительных дат, возможно благодаря предложенному здесь специальному приложению теории центральных мест. Приложение также позволяет установить ориентировочные размеры датированных поселений и определить радиус поиска памятников, отсутствующих в выборках. The particularity of the application of spatial analysis in archaeology is often caused by the insufficient information about expansion systems of the past. The usage of the character expression of M. Beckmann’s Central Place theory makes it possible to determine the size and number of settlements which are absent in samplings. Owing to the proposed special supplement of the Central Place theory, it is possible to connect them with specific sites which do not have clear relative dates. This supplement also allows to calculate approximate sizes of the dated settlements and to determine the search radius of sites which are absent in samplings.